Vitamin D Binding Protein as screening biomarker candidate for late-onset preeclampsia without intrauterine growth restriction during 16 week of gestation. - Nejadi, Naser; Hantoushzadeh, Sedigheh; Mohammadpoor Masti, Setareh; Sadat Hosseini, Zohreh; Mousavi, Masoumea; Gorgani-Firuzjaee, Sattar; Zali, Hakimeh; Rezaei Tavirani, Mostafa; Golmohammadi, Taghi (Archives of Advances in Biosciences, 2015)
The aim of this investigation was conducted to proteomic analysis of plasma obtained from pregnant women who destined to develop late-onset preeclampsia without intrauterine growth restriction (IUGR) during 16th week of gestation. Plasma was obtained from primiparous women during 16th week of gestation. 2-DE proteomic analysis was done for plasma from 11 healthy pregnant women and 11 women who developed preeclampsia later. Using bioinformatic analysis with Progenesis SameSpots ver4.0 software and ANOVA test, expression of 2 spots were statistically different between two groups. In preeclamptic state, expression of both were decreased, one of these spots was vitamin D binding protein (p-value: 0.047), the other one will be discussed in another paper. According to results, we concluded that during 16th week of gestation, occurance of late-onset preeclampsia without IUGR is predictable. During this week, pathology of disease is present and may be the process of placental degeneration and impaired placentation are include in disease pathology.